2011
DOI: 10.1111/j.1365-2648.2011.05812.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between in‐hospital mortality, readmission into the intensive care nursing unit and/or operating theatre and nurse staffing levels

Abstract: Higher nurse staffing levels on postoperative general nursing cardiac surgery units protected patients from unplanned readmission to intensive care units or operating theatre and in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 17 publications
4
39
0
2
Order By: Relevance
“…These findings are consistent with Aiken's initial report over a decade ago on the relationship between nurse education and patient mortality, 6 a number of smaller studies conducted in Europe, [7][8][9][10][11] as well as with a substantial body of international reports, [12][13][14][15] including more recent studies [16][17][18][19] that continue to affirm the beneficial relationship between higher percentages of nursing staff with bachelor's degrees and lower patient mortality.…”
Section: Study On Nurse Staffing and Education And Patient Mortalitysupporting
confidence: 79%
“…These findings are consistent with Aiken's initial report over a decade ago on the relationship between nurse education and patient mortality, 6 a number of smaller studies conducted in Europe, [7][8][9][10][11] as well as with a substantial body of international reports, [12][13][14][15] including more recent studies [16][17][18][19] that continue to affirm the beneficial relationship between higher percentages of nursing staff with bachelor's degrees and lower patient mortality.…”
Section: Study On Nurse Staffing and Education And Patient Mortalitysupporting
confidence: 79%
“…For example, in intensive care units (ICUs) higher RN staffing was associated with lower levels of hospital related mortality; each additional full time equivalent RN per patient day corresponds to a 9% reduction in odds of death in ICUs (ORs, 0.91; 95% CI 0.86 to 0.96), which would save 5 lives per 1000 patients. Although much of the reviewed research was undertaken in hospitals in the USA similar findings have been identified in other countries, for example, Belgium,8 9 Korea,10 11 and the UK 12. Other research shows that in some cases variation in staffing levels and patient outcomes within hospitals is greater than that between hospitals, which can mask the effect of any relationship between nurse staffing and patient outcomes 13.…”
Section: Introductionmentioning
confidence: 72%
“…Cheung, Aiken, Clarke, and Sloane (2008) identifi ed inadequate nurse staffi ng ratios to be related to poorer clinical outcomes (p. 36). Diya, Van den Heede, Sermeus, and Lesaffre (2012) found a relationship between higher nurse staffi ng levels on postoperative general nursing cardiac surgery units and lower unplanned readmission into the intensive care nursing unit and/or operating theatre. Similarly, Joynt and Jha (2011) found an association between higher nurse staffi ng level and lower readmission rates for heart failure (p. 58).…”
Section: F Actors R Elated To Ami R Eadmissionmentioning
confidence: 91%